Mission and Colonial Education in Africa - Ekpenyong, Ekpenyong Obo; Okoi, Ibiang O. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
There is no known civilization in the world whose root is not in the dominant religion. Catholic orders and Protestant denominations have not been heavily involved in providing mass education until the Reformation and Counter-Reformation. The motive for providing education has always been an altruistic concern for making or enhancing the quality of life of children to become better, and as an instrument to gain more followers. The greatest Christian missionaries' contribution to the Christian missionaries in Nigeria and in Africa was in the field of education. This work seeks to find the impact of mission and colonial educational system on Africa. This work has shown that the Western form of education was appreciated for producing the erudite and sophisticated elites in Africa. This work has also shown that the Colonial and the mission educational system were only concerned with having a literary form of education rather than technical and vocational bias and teaching its products to despise manual work. Hence refused to provide education in such fields like the science and technology profession which they know would rob them of their monopoly of significant positions and posts. This work adopts the qualitative method which used historical and content analysis. It concludes that perhaps rather fascinating to note that while a considerable measure of industrialization was achieved in white settlers dominated parts of Africa; black Africa had remained separated from the tide of industrialization.